Performances Of Initial Public Offerings On Information Communication Technology Companies In Malaysia 1998 -2004 - Hashim, Hairulnizam (2005)
This study examines the performances of Initial Public Offerings (IPO) on Information Communication Technology (ICT) companies in Malaysia. This study investigates the performances of IPOs by comparing with several market indices, IPOs on non-ICT Companies (control group) as well as different Board of listing and different year of listing.